Anthology of African Christianity - Phiri, Isabel Apawo; Werner, D. (Dietrich); Kaunda, Chammah (Chammah J.); Owino, Kennedy; Kalengyo, Edison M.; Djomhue, Priscille; Biri, Kudzai; Asamoah-Gyadu, J. Kwabena (Johnson Kwabena); Amanze, James; Hewitt, Roderick R. (Regnum studies in global Christianity., 2016)
By the beginning of the twenty-first century, Christianity has taken shape and established roots in all areas of African reality. It has come to stay. Therefore, we welcome Christianity afresh in Africa, where it has arrived to continue the ancient and vibrant Christianity in Egypt, Ethiopia, and Eritrea. It is appropriate that the Anthology of African Christianity presents, in valuable detail, this new reality that describes its African landscape in totality.